Analysis of Thrust & Torque B-Series Propeller using CFD: Variation of Blade and nProp - Mohammad Danil Arifin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
The propeller is an important part of determining the ship's maneuverability. The propeller itself is a tool to produce thrust that comes from engine power which is transmitted through the shaft. At their defined radial position, Propeller thrust (N) and torque (Nm) are formed from propeller blade foil sections at the local lift and drag. Particularly, the total propeller thrust will be integrated into an axial lift vector for the sections from root to tip. The selection of a good propulsion device will affect the force of the ship. One way to choose the propulsion of the ship is the selection the type of propeller and the provision of new propeller variations to produce maximum thrust. For that reason, this study aims to analyze of thrust and torque of B-series propellers using CFD by varying the number of blades: 3, 4, and 5 blades; and the propeller speed (nProp) i.e., 325, 525, and 725 rpm. The numerical analysis using computational fluid dynamics (CFD) was conducted to identify the thrust (N) and force (Nm) of the propeller. The CFD simulation consists of three main steps: pre-processor, solver manager, and post-processor. The results show that the thrust and torque significantly increased at the higher number of blades and nProp.